Marketing communications : principles and practice - Kitchen, Philip J. (International Thomson Business Press, 1999)
This book is about: The role and function of marketing communications in organizations; The evolution of marketing and marketing communications; Planning the marketing communications process; The organizational context of marketing communication; ...